MORAL SELF-CONSCIOUS HIGH SCHOOL STUDENTS (GENERAL DESCRIPTION FEATURES AND FORMATION) - Ternopilska, Valentina I. (Educological discourse, 2014)
The article deals with the concept of moral consciousness of personality. Age characteristics of senior pupils in the context of moral consciousness formation are outlined. Features of a teacher preparation for moral consciousness formation of a senior pupil are characterized.